1999
DOI: 10.1046/j.1464-410x.1999.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

The responsiveness of the ICSmale questionnaire to outcome: evidence from the ICS‐‘BPH’ study

Abstract: The ICSmale questionnaire, in addition to being psychometrically valid and reliable, is responsive to change in outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…This study builds on the development of other instruments designed to assess LUTS, such as the IPSS (7,11), ICIQ-MLUTS and ICIQ-BFLUTS (8)(9)(10), and DAN-PSS (12,13), which have been widely used in epidemiological studies and clinical trials. Findings from the qualitative research reported here point to both the strengths and the weaknesses of these individual instruments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study builds on the development of other instruments designed to assess LUTS, such as the IPSS (7,11), ICIQ-MLUTS and ICIQ-BFLUTS (8)(9)(10), and DAN-PSS (12,13), which have been widely used in epidemiological studies and clinical trials. Findings from the qualitative research reported here point to both the strengths and the weaknesses of these individual instruments.…”
Section: Discussionmentioning
confidence: 99%
“…This qualitative research is useful to clinicians to understand what patients want when considering treatments for LUTS. ORIGINAL PAPER ª 2010 Blackwell Publishing Ltd Int J Clin Pract, August 2010, 64, 9,[1260][1261][1262][1263][1264][1265][1266][1267][1268][1269][1270][1271][1272][1273][1274][1275][1276][1277][1278] defined by the ICS are 'subjective indicator(s) of disease or change in condition as perceived by the patient, caregiver or partner' (1). Unfortunately, research to evaluate content validity is often given insufficient attention from researchers (4).…”
Section: What's Newmentioning
confidence: 99%
See 1 more Smart Citation
“…1,8,12 Focus groups, which typically involve 6-10 people with a common attribute, such as a disease, can have advantages over individual interviews in that descriptions of the patient experience are enriched by participants' responses to the comments of others. 10 Conversely, personal or sensitive topics may be better suited for one-on-one interviews or 40,41 Detailed assessment of male lower urinary tract symptoms and associated bother gender-specific groups. Focus groups and one-to-one interviews should be conducted by moderators with experience in qualitative methods, following a semi-structured interview or discussion guide.…”
Section: Conducting Qualitative Researchmentioning
confidence: 99%
“…The questionnaire is also responsive, showing sensitivity to expected changes after a range of treatments, i.e. TURP, drug therapies, minimally invasive therapies and watchful waiting [27].…”
Section: The Assessment Of Lutsmentioning
confidence: 99%